Designs, facilitators, barriers, and lessons learned during the implementation of emergency department led virtual urgent care programs in Ontario, Canada - Hall, Justin N.; Ackery, Alun D.; Dainty, Katie N.; Gill, Paul S.; Lim, Rodrick; Masood, Sameer; McLeod, Shelley L.; Mehta, Shaun D.; Nijmeh, Larry; Rosenfield, Daniel; Rutledge, Greg; Verma, Aikta; et al. (Frontiers in Digital Health, 2022)
Introduction Virtual patient care has seen incredible growth since the beginning of the COVID-19 pandemic. To provide greater access to safe and timely urgent care, in the fall of 2020, the Ministry of Health introduced a pilot program of 14 virtual urgent care (VUC) initiatives across the province of Ontario. The objective of this paper was to describe the overall design, facilitators, barriers, and lessons learned during the implementation of seven emergency department (ED) led VUC pilot programs in Ontario, Canada. Methods We assembled an expert panel of 13 emergency medicine physicians and researchers with experience leading and implementing local VUC programs. Each VUC program lead was asked to describe their local pilot program, share common facilitators and barriers to adoption of VUC services, and summarize lessons learned for future VUC design and development. Results Models of care interventions varied across VUC pilot programs related to triage, staffing, technology, and physician remuneration. Common facilitators included local champions to guide program delivery, provincial funding support, and multi-modal marketing and promotions. Common barriers included behaviour change strategies to support adoption of a new service, access to high-quality information technology to support new workflow models that consider privacy, risk, and legal perspectives, and standardized data collection which underpin overall objective impact assessments. Conclusions These pilot programs were rapidly implemented to support safe access to care and ED diversion of patients with low acuity issues during the COVID-19 pandemic. The heterogeneity of program implementation respects local autonomy yet may present challenges for sustainability efforts and future funding considerations.